Software libre y libre acceso a la información: ¿Hacia un ciberespacio público? - Zurita Sánchez, Juan Manuel; Torres Vargas, Georgina Araceli (Documentación de las Ciencias de la Información, 2007)
In the context of the free access to the information and the democratization of the knowledge, the present paper is focused in describing the current state of some proposals related with the cooperation and the world exchange of information, arisen starting from the XX century, but mainly in the movement of the free software that is profiled as a model of informational development in agreement to the cultural movements of our days, and whose principles, it is omened, they can end up being the base for the creation of a public cyberspace, supported in services of information to low cost and digital libraries of world reach.